Expression of miRNA-106b in conventional renal cell carcinoma is a potential marker for prediction of early metastasis after nephrectomy - Slaby, Ondrej (BioMed Central, 2010)
BACKGROUND: MicroRNAs are endogenously expressed regulatory noncoding RNAs. Previous studies have shown altered expression levels of several microRNAs in renal cell carcinoma. METHODS: We examined the expression levels of selected microRNAs in 38 samples of conventional renal cell carcinoma (RCC) and 10 samples of non-tumoral renal parenchyma using TaqMan real-time PCR method. RESULTS: The expression levels of miRNA-155 (p < 0.0001), miRNA-210 (p < 0.0001), miRNA-106a (p < 0.0001) and miRNA-106b (p < 0.0001) were significantly over-expressed in tumor tissue, whereas the expression of miRNA-141 (p < 0.0001) and miRNA-200c (p < 0.0001) were significantly decreased in RCC samples. There were no significant differences between expression levels of miRNA-182 and miRNA-200b in tumor samples and renal parenchyma. Our data suggest that expression levels of miRNA-106b are significantly lower in tumors of patients who developed metastasis (p = 0.030) and miR-106b is a potential predictive marker of early metastasis after nephrectomy in RCC patients (long-rank p = 0.032). CONCLUSIONS: We have confirmed previous observations obtained by miRNA microarray analysis using standardized real-time PCR method. For the first time, we have identified a prognostic significance of miRNA-106b, which, after validation on a larger group of patients, maybe useful as a promising biomarker in patients with RCC.